Cue-elicited heart rate variability and attentional bias predict alcohol relapse following treatment - Garland, Eric L.; Franken, Ingmar H. A.; Howard, Matthew O. (Psychopharmacologia, 2012)
Rationale Identification of malleable neurocognitive predictors of relapse among alcohol-dependent individuals is important for the optimization of health care delivery and clinical services. Objectives Given that alcohol cue-reactivity can predict relapse, we evaluated cue-elicited high-frequency heart rate variability (HFHRV) and alcohol attentional bias (AB) as potential relapse risk indices. Method Alcohol-dependent patients in long-term residential treatment who had participated in mindfulness-oriented therapy or an addiction support group completed a spatial cueing task as a measure of alcohol AB and an affect-modulated alcohol cue-reactivity protocol while HFHRV was assessed. Results Post-treatment HFHRV cue-reactivity and alcohol AB significantly predicted the occurrence and timing of relapse by 6-month follow-up, independent of treatment condition and after controlling for alcohol dependence severity. Alcohol-dependent patients who relapsed exhibited a significantly greater HFHRV reactivity to stress-primed alcohol cues than patients who did not relapse. Conclusions Cue-elicited HFHRV and alcohol AB can presage relapse and may therefore hold promise as prognostic indicators in clinical settings.